Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's go through the calculations step-by-step.
1. For the first expression, [tex]\(32^{-\frac{3}{5}}\)[/tex]:
[tex]\[ 32^{-\frac{3}{5}} = \left( \frac{1}{32} \right)^{\frac{3}{5}} \][/tex]
First, observe that 32 can be written as [tex]\(2^5\)[/tex]:
[tex]\[ 32 = 2^5 \][/tex]
Thus,
[tex]\[ 32^{-\frac{3}{5}} = (2^5)^{-\frac{3}{5}} \][/tex]
Using the property of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (2^5)^{-\frac{3}{5}} = 2^{5 \cdot -\frac{3}{5}} = 2^{-3} \][/tex]
Now, calculate [tex]\(2^{-3}\)[/tex]:
[tex]\[ 2^{-3} = \frac{1}{2^3} = \frac{1}{8} = 0.125 \][/tex]
So,
[tex]\[ 32^{-\frac{3}{5}} = 0.125 \][/tex]
2. For the second expression, [tex]\(\left(\frac{1}{9}\right)^{\frac{3}{2}}\)[/tex]:
Rewrite [tex]\(1/9\)[/tex] as [tex]\(9^{-1}\)[/tex]:
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} = \left(9^{-1}\right)^{\frac{3}{2}} \][/tex]
Using the property of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ \left(9^{-1}\right)^{\frac{3}{2}} = 9^{-\frac{3}{2}} \][/tex]
Now express 9 as [tex]\(3^2\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Thus,
[tex]\[ 9^{-\frac{3}{2}} = (3^2)^{-\frac{3}{2}} \][/tex]
Applying the property of exponents again:
[tex]\[ (3^2)^{-\frac{3}{2}} = 3^{2 \cdot -\frac{3}{2}} = 3^{-3} \][/tex]
Now, calculate [tex]\(3^{-3}\)[/tex]:
[tex]\[ 3^{-3} = \frac{1}{3^3} = \frac{1}{27} \approx 0.037037037037037035 \][/tex]
So,
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} \approx 0.037037037037037035 \][/tex]
In summary, we have:
[tex]\[ 32^{-\frac{3}{5}} = 0.125 \][/tex]
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} \approx 0.037037037037037035 \][/tex]
1. For the first expression, [tex]\(32^{-\frac{3}{5}}\)[/tex]:
[tex]\[ 32^{-\frac{3}{5}} = \left( \frac{1}{32} \right)^{\frac{3}{5}} \][/tex]
First, observe that 32 can be written as [tex]\(2^5\)[/tex]:
[tex]\[ 32 = 2^5 \][/tex]
Thus,
[tex]\[ 32^{-\frac{3}{5}} = (2^5)^{-\frac{3}{5}} \][/tex]
Using the property of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (2^5)^{-\frac{3}{5}} = 2^{5 \cdot -\frac{3}{5}} = 2^{-3} \][/tex]
Now, calculate [tex]\(2^{-3}\)[/tex]:
[tex]\[ 2^{-3} = \frac{1}{2^3} = \frac{1}{8} = 0.125 \][/tex]
So,
[tex]\[ 32^{-\frac{3}{5}} = 0.125 \][/tex]
2. For the second expression, [tex]\(\left(\frac{1}{9}\right)^{\frac{3}{2}}\)[/tex]:
Rewrite [tex]\(1/9\)[/tex] as [tex]\(9^{-1}\)[/tex]:
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} = \left(9^{-1}\right)^{\frac{3}{2}} \][/tex]
Using the property of exponents [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ \left(9^{-1}\right)^{\frac{3}{2}} = 9^{-\frac{3}{2}} \][/tex]
Now express 9 as [tex]\(3^2\)[/tex]:
[tex]\[ 9 = 3^2 \][/tex]
Thus,
[tex]\[ 9^{-\frac{3}{2}} = (3^2)^{-\frac{3}{2}} \][/tex]
Applying the property of exponents again:
[tex]\[ (3^2)^{-\frac{3}{2}} = 3^{2 \cdot -\frac{3}{2}} = 3^{-3} \][/tex]
Now, calculate [tex]\(3^{-3}\)[/tex]:
[tex]\[ 3^{-3} = \frac{1}{3^3} = \frac{1}{27} \approx 0.037037037037037035 \][/tex]
So,
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} \approx 0.037037037037037035 \][/tex]
In summary, we have:
[tex]\[ 32^{-\frac{3}{5}} = 0.125 \][/tex]
[tex]\[ \left(\frac{1}{9}\right)^{\frac{3}{2}} \approx 0.037037037037037035 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.